2023
DOI: 10.1186/s13102-023-00651-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of echocardiographic parameters of amputee football players with active football players and sedentary individuals

Abstract: Background The purpose of this study is to compare the echocardiographic (ECHO) parameters of amputee football players (AF) with those of athletes without a disability (football players) (FP), and sedentary individuals (SI). Methods A total of 37 male participants (nAF = 12, nFP = 12, nSI = 13) were included in the study. All participants underwent a transthoracic echocardiographic examination. Aortic diameter in systole (ADs), aortic diameter in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…This indicates there is no enlargement in atrial chambers of the heart in AF group. This was indeed was further confirmed in our previous echocardiography study in AF population ( Kurtoğlu et al, 2023 ). However, P-wave amplitude was higher in amputee football players than in other two disabled groups though it was not a pathological elevation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This indicates there is no enlargement in atrial chambers of the heart in AF group. This was indeed was further confirmed in our previous echocardiography study in AF population ( Kurtoğlu et al, 2023 ). However, P-wave amplitude was higher in amputee football players than in other two disabled groups though it was not a pathological elevation.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the AF group was compared with healthy individuals. In a recent study, AF individuals and healthy football players and sedentary individuals were compared with echocardiography, and left ventricular end diastolic diameter and early diastole values of AFs were found to be lower than healthy football players and sedentary individuals, and left ventricular posterior wall thickness was found to be higher in AF group ( Kurtoğlu et al, 2023 ). These results confirm that individuals with amputation have a different cardiac structure than healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, it can be concluded that the excessive training load applied to amputees causes fatigue in the heart and skeletal muscles. In our previous studies, it was concluded that the heart morphology of amputees is different from that of healthy individuals [22]. In this research, the sample consisted of amputee soccer players.…”
Section: Discussionmentioning
confidence: 92%
“…The most important cause of postamputation mortality (39% survival rate at 7 years) in amputees is cardiac problems [21]; therefore, it is necessary to examine the physiological and morphological development of different types of exercise on the heart in these individuals. In our latest research, we have shown that the echocardiographic findings of amputee soccer players differ from those of nonamputee athletes and sedentary individuals [22]. This finding suggested that exercise has different morphological effects on the hearts of amputees.…”
Section: Introductionmentioning
confidence: 95%